Glass-Ceramics with Co:Ga2O3 Nanocrystals: A Saturable Absorber for 1.5-1.7 μm Erbium Lasers - LOIKO, P. A.; SKOPTSOV, N. A.; YUMASHEV, K. V.; GLAZUNOV, I. V.; MALYAREVICH, A. M.; DYMSHITS, O. S.; ZHILIN, A. A.; ALEKSEEVA, I. P.; ZAPALOVA, S. S.; VITKIN, V. V.; KHARITONOV, A. A. (PHYSICS, CHEMISTRY AND APPLICATIONS OF NANOSTRUCTURES, 2015)
Transparent glass-ceramics containing γ-Ga2O3:Co2+ nanocrystals are synthesized in the lithium gallium silicate system. The observed red-shift of the absorption band related to the 4A2g(4F)→4T1g(4F) transition of Co2+ ions in tetrahedral sites and absorption saturation properties indicate that the glass-ceramics is suitable for the Q-switching of 1.5-1.7 μm eye-safe erbium lasers. Passively Q-switched Er,Yb:glass diode-pumped laser delivering 1.75 mJ of 25 ns-long pulses at 1540 nm is realized.